Simple detection of Bacillus anthracis spores by precipitation method with goat antibody anti anthrosa - Parwanto, M. L. Edy; Pakpahan, Alfred; Edy, Hosea Jaya (International Journal of Research in Medical Sciences, 2016)
Background: Bacillus anthracis has a potential for biological weapon or bioterorism. Attack of Bacillus anthracis is very fatal, and the distribution is very easy and cheap through the spores. The aim of this was study to detect the spores of Bacillus anthracis. Methods: Bacillus anthracis isolates were grown on serum agar and then sheep blood medium, to stimulate capsule formation. Spores which formed painted using the method of Schaefer and Fultton. The methods of precipitation and immuno-chromatography were used to spores detection of Bacillus anthracis. Results: Painting with Schaeffer and Fulton method showed that spores of Bacillus anthracis are green. Precipitation reaction between spores of Bacillus anthracis with goat antibody anti anthrosa was resulting in a silver white color. Anthrosa of Bacillus anthracis spores was detected by means of immuno-chromatography using goat antibody anti anthrosa. The molecular weight of anthrosa is ±148 kDa. Conclusions: The methods of precipitation and immuno-chromatography using goat antibody anti anthrosa can be used to detection of Bacillus anthracis spores. Goat antibody anti anthrosa can react positively with Bacillus anthracis spores.